Al-Bashri Boarding School's Strategic Steps to Prepare Indonesia's Golden Generation 2045 - Ade Salamun (Journal of Multi-Disciplines Science, 2025)
Education in Indonesia has undergone various changes since independence, reflecting the dynamics of the development of the education system that continues to adapt to the challenges of the times. This article discusses the role of teachers and parents in education, the concept of education according to the Prophet Muhammad SAW, and the challenges in implementing Islamic education in Indonesia today. The methods used in writing this article are qualitative w, descriptive approach, and a literature study. The discussion results show that teachers have a central role in shaping the character and intelligence of students. From the Islamic education perspective, teachers act as teachers and guides who instill the values ​​of manners and good morals. As the Qur'an commands, Parents are primarily responsible for educating their children. So education during the Prophet Muhammad SAW took 24 hours, from early childhood education to higher education. The education of the Prophet SAW emphasized the importance of integration between knowledge and manners, which needs to be applied continuously throughout life. However, Islamic education in Indonesia faces significant challenges, such as digitalization that changes learning methods, the dichotomy between religious knowledge and general knowledge, and the influence of secular culture. Therefore, it is necessary to revitalize the curriculum and integrate Islamic values ​​in all aspects of education to produce a civilized and knowledgeable generation. Thus, the Islamic education system can remain relevant and face the challenges of the modern era.